The Pyrolytic Profile of Lyophilized and Deep-Frozen Compact Part of the Human Bone - Jolanta Lodowska; Daniel Wolny; Sławomir Kurkiewicz; Ludmiła Węglarz (The Scientific World Journal)
Background. Bone grafts are used in the treatment of nonunion of fractures, bone tumors and in arthroplasty. Tissues preserved by lyophilization or deep freezing are used as implants nowadays. Lyophilized grafts are utilized in the therapy of birth defects and bone benign tumors, while deep-frozen ones are applied in orthopedics. The aim of the study was to compare the pyrolytic pattern, as an indirect means of the analysis of organic composition of deep-frozen and lyophilized compact part of the human bone. Methods. Samples of preserved bone tissue were subjected to thermolysis and tetrahydroammonium-hydroxide- (TMAH-) associated thermochemolysis coupled with gas chromatography and mass spectrometry (Py-GC/MS). Results. Derivatives of benzene, pyridine, pyrrole, phenol, sulfur compounds, nitriles, saturated and unsaturated aliphatic hydrocarbons, and fatty acids (C12–C20) were identified in the pyrolytic pattern. The pyrolyzates were the most abundant in derivatives of pyrrole and nitriles originated from proteins. The predominant product in pyrolytic pattern of the investigated bone was pyrrolo[1,2-α]piperazine-3,6-dione derived from collagen. The content of this compound significantly differentiated the lyophilized graft from the deep-frozen one. Oleic and palmitic acid were predominant among fatty acids of the investigated samples. The deep-frozen implants were characterized by higher percentage of long-chain fatty acids than lyophilized grafts.